Energy from the Bowels of the Earth. Vulcanism and Its Uses in Iceland - Machol,Robert E (1980)
Iceland is far ahead of the rest of the world in the use of geothermal energy for hot water and space heating, but they have run into severe difficulties in generating electricity from this source. The present report describes these difficulties and some of the people involved. (Author)